Experimental Study on Flexural Performance of Sun-Dried Bamboo (Nigalo) Reinforced Concrete Beams - Dhungana, Subigya; Adhikari, Sandeep; Ayer, Prakash; Ghimire, Roshan; Aryal, Sandesh; Paudel, Sanjaya; Tiwari, Saugat; Baral, Sanjay (Journal of Engineering Technology and Planning, 2025)
Arundinaria falcata is a fast-growing, renewable bamboo species locally called Nigalo in Nepal, offers a sustainable option for reinforcement material. This study investigates the structural performance of concrete beams reinforced with Nigalo, known for its high flexural performance and local availability. The goal is to explore untreated Nigalo as a sustainable alternative to steel reinforcement in concrete structures. The research focuses on understanding the compatibility of Nigalo with concrete and valuating its mechanical behavior, particularly in terms of flexural strength. An experimental analysis was carried out using sun-dried Nigalo as reinforcement in concrete beams. Tests included flexural strength measurements, as well as assessments of moisture absorption. The interaction between the Nigalo and the cement matrix was also studied to understand long-term performance and environmental resistance. The results showed that Nigalo reinforced beams performed better than plain concrete beams, with strength increases of 19.30%, 64.30%, and 83.72% at reinforcement levels of 1%, 2.55%, and 3.88%, respectively. However, challenges remain due to Nigalo’s vulnerability to moisture and biodegradation within the concrete. These findings suggest that while Nigalo has potential as a cost-effective and eco-friendly reinforcement material, further research is needed on protective treatments to improve its durability. This study contributes to the growing interest in sustainable building materials and highlights Nigalo’s potential use is abundant. It supports the broader goal of reducing reliance on non-renewable construction materials through the use of locally available renewable alternatives.